Rupture of Hepatic Artery Aneurysm as a Cause of Severe Upper Gastrointestinal Bleeding and Cholangitis in a Liver Transplanted Patient - Efe, Cumali; Batıbay, Ersin; Yüksekyayla, Osman; Kolu, Mehmet (Turkish Journal of Gastroenterology, 2024)
Cite this article as: Efe C, Batıbay E, Yüksekyayla O, Kolu M. Rupture of hepatic artery aneurysm as a cause of severe upper gastrointestinal bleeding and cholangitis in a liver transplanted patient. Turk J Gastroenterol. 2024;35(8):675-676.